Relative Consumption, Working Time, and Trade Unions - Laszlo Goerke; Inga Hillesheim (Center for Economic Studies and ifo Institute (CESifo), 2013)
Status considerations with respect to consumption give rise to negative externalities because individuals do not take into account that their decisions affect the relative consumption position of others. Further, status concerns create incentives for excessive labour supply in competitive markets. We show that trade unions which are unable to internalise the externality can nevertheless mitigate the resulting distortion. The reason is that wages above the market clearing level are only feasible if people work less and, therefore, fewer hours than in a competitive market. Accordingly, the theoretical model establishes that trade unions can have a welfare-enhancing role in a world with relative consumption effects.
Keywords: D62; J22; J51; 330; externality; hours of work; relative consumption; trade union